Adaptation of Rehabilitation Courses Based on MRI Biomarkers in Multiple Sclerosis: Clinical-Radiological Approach (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Multiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system, leading to progressive neurological impairments. Rehabilitation plays a crucial role in improving functional outcomes for MS patients, yet individual approaches are often needed to tailor treatment to the unique needs of each patient. Magnetic resonance imaging (MRI) biomarkers, such as lesions and diffusion abnormalities, provide a non-invasive method to assess the severity and progression of the disease. This study explores how MRI biomarkers can be used to adapt rehabilitation courses in MS patients, ensuring a more personalized and effective recovery process. A clinical-radiological approach was employed to monitor the impact of MRI on rehabilitation strategy optimization. The results showed that MRI-guided rehabilitation not only improved motor function but also enhanced cognitive performance, demonstrating the potential of MRI biomarkers in refining rehabilitation courses. This approach could significantly contribute to more precise, evidence-based treatment regimens for MS patients, promoting faster and more efficient recovery.